A Novel Concept for Partial Liver Transplantation in Nonresectable Colorectal Liver Metastases: The RAPID Concept. Issue 1 (July 2015) - Line, Pål-Dag; Hagness, Morten; Berstad, Audun Elnaes; Foss, Aksel; Dueland, Svein
Abstract : Objective: Selected patients with nonresectable colorectal liver metastases benefit from liver transplantation and have acceptable 5-year survival rates. However, allocating full-sized grafts to this group of patients is difficult due to the scarcity of grafts. This could be improved by utilizing small partial grafts, which mandates effective strategies to overcome the problems regarding insufficient functional liver mass. Methods: We have developed a protocol incorporating previously reported experiences from living donor transplantation and recent developments in liver surgery, facilitating transplantation of very small liver grafts. At the time of transplantation, segments 1 to 3 are resected in the recipient and orthotopically replaced by a segment 2 to 3 allograft. Portal inflow is modulated by redirecting the portal flow to the graft with concomitant focus on keeping the portal vein pressure below 20 mm Hg. A second-stage hepatectomy is performed as soon as the graft has regenerated to a sufficient volume. Results: A graft weighing 330 g was transplanted to a 50-year-old man weighing 92 kg, and the portal vein to the right remnant liver was closed. The volume of the liver graft was doubled 2 weeks after the first procedure, and it increased further after the second procedure, with extended right hepatectomy performed at day 23 after transplantation. There were no signs of liver failure or small-for-size syndrome. Conclusions: The current protocol and ongoing study could represent a possible strategy to increase the availability of liver transplantation to patients with nonresectable liver tumors such as hepatocellular carcinoma and colorectal liver metastases.